Facts and fantasies about superior mesenteric artery syndrome: an unusual cause of intestinal obstruction - Kushwaha, Swapnil Singh; Goja, Shikha (International Surgery Journal, 2019)
Superior mesenteric artery (SMA) syndrome (also known as Wilkie’s syndrome) is an unusual cause of proximal intestinal obstruction, attributable to vascular compression of the third part of duodenum between the superior mesenteric artery and the abdominal aorta due to acute angulation of SMA. It is a life threatening disease as it poses a diagnostic dilemma and often diagnosed by exclusion of other causes. It is an acquired disorder and is commonly due to loss of fatty tissue as a result of a variety of debilitating conditions. We report a case of SMA syndrome in a 23 year young asthenic female patient, with a long history of recurrent abdominal pain, epigastric fullness, voluminous vomiting, and weight loss. Symptoms persisted for 1 year and the patient underwent extensive investigations, but to no avail. Thereafter she developed proximal intestinal obstruction, which unravelled her diagnosis. Abdominal examination revealed epigastric fullness, tenderness and hyper peristaltic bowel sounds. We performed small bowel enteroclysis, upper gastrointestinal series, abdominal computer-tomography (CT) and ultrasonography to establish the diagnosis. Conservative treatment was tried for one month but failed. There was no relief of symptoms in the left lateral decubitus or prone position. Finally, the patient successfully underwent Roux-en-Y duodenojejunal anastomosis with a postoperative favourable outcome. This case emphasizes the challenges in the diagnosis of SMA syndrome and the need for increased awareness of this entity. This will improve early recognition in order to reduce irrelevant tests and unnecessary treatments.